Diarylheptanoids from Alnus viridis ssp. viridis and Alnus glutinosa: Modulation of Quorum Sensing Activity in Pseudomonas aeruginosa - Ilic-Tomic, Tatjana; Sokovic, Marina; Vojnovic, Sandra; Ciric, Ana; Veljic, Milan; Nikodinovic-Runic, Jasmina; Novakovic, Miroslav (Planta Medica, 2017)
Diarylheptanoids from the barks of Alnus viridis ssp. viridis (green alder) and Alnus glutinosa (black alder) were explored for anti-quorum sensing activity. Chemicals with anti-quorum sensing activity have recently been examined for antimicrobial applications. The anti-quorum sensing activity of the selected diarylheptanoids was determined using two biosensors, namely Pseudomonas aeruginosa PAO1 and Chromobacterium violaceum CV026. Although all of the investigated compounds negatively influenced the motility of P. aeruginosa PAO1, four were able to inhibit biofilm formation of this human opportunistic pathogen for 40–70 %. Three of the diarylheptanoids (3, 4, and 5) negatively influenced the biosynthesis of pyocyanin, which is under the control of quorum sensing. Platyphyllenone (7) and hirsutenone (5) were able to inhibit the biosynthesis of violacein in C. violaceum CV026, with 5 being able to inhibit the synthesis of both biopigments. Only one of the tested diarylheptanoids (1) was shown to significantly decrease the production of acyl homoserine lactones (AHL) in P. aeruginosa PAO1, more specifically, production of the long chain N-(3-oxododecanoyl)-l-HSL. On the other side, four diarylheptanoids (2–5) significantly reduced the synthesis of 2-alkyl-4-quinolones, part of the P. aeruginosa quinolone-mediated signaling system. To properly assess therapeutic potential of these compounds, their in vitro antiproliferative effect on normal human lung fibroblasts was determined, with doses affecting cell proliferation between 10 and 100 µg/mL. This study confirms that the barks of green and black alders are rich source of phytochemicals with a wide range of biological activities that could further be exploited as natural agents against bacterial contaminations and infections.
Keywords: Alnus viridis ssp. viridis; Alnus glutinosa; Betulaceae; diarylheptanoids; quorum sensing; acyl homoserine lactone; Pseudomonas aeruginosa